Problem-Based Learning Model Assisted by Graphic Media in Poetry Text Learning for Fourth Grade Elementary School Students - Ita Rosita; Abdul Rozak; Dede Endang Mascita (International Journal of Educational Research Excellence (IJERE), 2024)
This research aims to explain the problem-based learning model assisted by graphic media in learning poetry texts for fourth-grade elementary school students, as well as the process of implementing it in learning. The research was conducted in the 2022/2023 Academic Year, Even Semester, at Madrasah Ibtidaiyah Al-Zaytun, Sandrem Village, Gantar District, Indramayu Regency, with fourth-grade students in West Java Province. This research uses the Research and Development (R&D) method. The research design used is research and development (Research and Development) with the ADDIE model. The steps/phases of development include: Analysis, Design, Development or Production, Implementation or Delivery, and Evaluation. Data collection methods include interviews, questionnaires, observations, written tests, and performance assessments. The results of the research show that the design of a problem-based learning model assisted by graphic media in learning poetry texts for fourth-grade elementary school students is a new learning model developed from a problem-based learning model associated with graphic media, making learning more meaningful. The assessment results of the learning model design and media use were 70.5%, categorized as suitable for use. The learning media expert assessment results of 80% indicate that the learning media is suitable for use. Meanwhile, based on the results of the implementation of the problem-based learning model assisted by graphic media in learning poetry texts, the assessment results were 38 out of 44, or 86.4%, indicating that the implementation of the learning model was very suitable for use. Based on the data above, it is evident that a problem-based learning model assisted by graphic media in learning poetry texts for fourth-grade elementary school students is highly needed.